Evaluation of Trichoderma spp. against Wirestem Disease of Cauliflower Caused by Rhizoctonia solani - Budha, Chandra Bahadur; Shrestha, Sundar Man; Manandhar, Hira Kaji; Baidya, Suraj (Journal of Agriculture and Environment, 2023)
The biological effectiveness of twenty-eight native isolates of Trichoderma along with two known species (Trichoderma viride and Trichoderma harzianum) were tested against Rhizoctonia solani using dual culture technique. Of them, seven isolates and the two species of Trichoderma were tested in pot culture under net-house conditions against wirestem disease of cauliflower caused by R. solani. Inhibitory effects on dual culture were statistically very significant for all tested Trichoderma. Thirteen Trichoderma isolates exhibited more than 90% bio-control index and twenty-three isolates had more or at par with T. viride and T. harzianum. In an in-vitro trial, isolate from Dhankuta (Pakhribas) was most effective against R. solani as evident by the highest bio-control index at 6 days after incubation. Similar to this, in an in-vivo experiment, tested isolates of Trichoderma contributed more or less in the plant canopy area, root length and shoot circumference attributes. Trichoderma isolates significantly contributed to root dry matter and biomass while there was a highly significant difference in reduction of disease severity. T. harzianum and the isolate from Dhankuta (Pakhribas) were most effective for the control of wirestem disease